ANALISIS KENDARAAN BERMOTOR RODA DUA BERDASARKAN (BOK) DESA TUMPOK LADANG KECAMATAN KAWAY XVI - Meidia Refiyanni; H Zakia; Teuku Cut Adek (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2016)
This study was conducted to analize and identify the factors which will affect the operational cost of two-wheel motor vehicles (motorcycle), analyzing vehicle operating costs of two-wheel motorvehicles (motorcycle) and determining an adequate model for the operational cost of two-wheel motor vehicles (motorcycle) in  Tumpuk Ladang Village Kaway XVI Sub District. The dependentvariable is the journey that affect operational cost, while  the independent variable is the cost of fuel consumption cost of oil ( engine oil and transmission oil), the cost of replacemet tires (tire andinner tube), the cost of implementation of the service, the cost of spare parts and unexpected cost In conducting statistical test, processing data using statistical SPSS software. Then after the statistical test, followed by calculating the operational cost of vehicles of vehicles by type, capacity and the assembly which includes fixed cost and variable cost. Based on the results of this study the cost of fuel consumption and tire replacement is the most influence on operational cost. Model of vehicle operating cost analysis for motorcyle in Tumpok Ladang Village adalah Y = 78,426 + 0,004 X1 + 0,001X2 – 0,012X3 + 0,211X4 – 0,929X5 + 0,002X6.